Strategi Penataan Kawasan Perdagangan Dan Jasa Melalui Pendekatan Tata Bangunan Lingkungan (Studi Kasus Cikarang Utara) - Bachtiar, Zeno; Zefri; supriyatno, budi (Magister Kajian Pembangunan Perkotaan dan Wilayah, 2023)
North Cikarang District is an area that is developing rapidly so there is a need to control high density blocks, the area has developed rapidly in the last 10 years. The growth of the city population has an impact on the increasing development of trade and service corridors on strategic main roads. This trend can continue considering that land values are increasing and the land around RTH is very strategic in location, so the development of multi-story buildings needs to be controlled, so that the composition of vertical and horizontal space is maintained. The analysis techniques used in this research are qualitative descriptive analysis and Geographic Information System analysis. The aim of using this approach is to describe people's behavior, field events, and certain activities in detail and in depth. What is meant by descriptive research is research simply to describe a variable relating to the problem being studied without questioning the relationship between variables. The results of this research obtained several strategies for utilizing the space of trade and service areas in the North Cikarang urban area, including: 1) 35% of the development monitoring process carried out in North Cikarang City has not paid attention to the IMB provisions, such as exceeding GSB, KDB, KDH, and even not have an IMB such as a residence; 2) There is no space provided for the Street Vendors (PKL) area in North Cikarang Urban Center; 3) Making the North Cikarang area an area of green open space and public space; 4) Limiting development that occurs in the North Cikarang area; 5) Conduct outreach regarding the importance of community participation in maintaining green open space areas as conservation areas; 6) Take action against violations of space use in the North Cikarang area that are not in accordance with the spatial planning plan.